Characterization of sub-systems of Brachiaria grassland in herds from humid tropic, Caquetá, Colombia (2018)
This study aims at characterizing the sub-systems of Brachiaria grasslands in humid tropic herds in five municipalities of the department of Caquetá, Colombia. To achieve this, we selected 20 farms with predominance of B. decumbes and B. humidicola, and divided the study into two phases: 1) static, in which we measured the socio-economic and the biophysical variables of the farm, the meadows, and the animals through characterization sheets; and 2) dynamic, in which we evaluated the productive performance of grasslands and animals. The qualitative variables were analyzed by contingence tables and correspondence analysis; while the quantitative variables, by descriptive statistics and, subsequently, multivariate statistics (PCA and clusters). The farms have 83±11 % of area in grasslands, 100 % divide and rotate the meadows, with periods of occupation of 3.71±3.33 days; in addition, 15 % of the farms have protein banks, 85 % depend on livestock activity, 80 % are owner managed, and 10% amend the soil. Weed control varies among mechanical, chemical, and mixed. The productivity of dry matter was 1,825.93±905.92 kg/ha/court, the grassland load capacity was 0.73 AU/ha, with milk yield of 1,492.95±416.55 kg/ha/year. In conclusion, the studied farms are dual-purpose family farms, with moderate technification and productivity.